An Artificial Mechano‐Nociceptor with Mott Transition. Issue 10 (9th September 2021) - Kumar, Mohit; Park, Ji‐Yong; Seo, Hyungtak
Abstract: Intelligent touch sensing is now becoming an essential part of various human‐machine interactions and communication, including in touchpads, autonomous vehicles, and smart robotics. Usually, sensing of physical objects is enabled by applied force/pressure sensors; however, reported conventional tactile devices are not able to differentiate sharp and blunt objects, although sharp objects can cause unavoidable damage. Therefore, it is central issue to implement electronic devices that can classify sense of touch and simultaneously generate pain signals to avoid further potential damage from sharp objects. Here, concept of force‐enabled nociceptive behavior is proposed and demonstrated using vanadium oxide‐based artificial receptors. Specifically, versatile criteria of bio‐nociceptor like threshold, relaxation, no adaptation, allodynia, and hyperalgesia behaviors are triggered by pointed force, but the device does not mimic any of these by the force applied by blunt objects; thus, the proposed device classifies the intent of touch. Further, supported by finite element simulation, the nanoscale dynamic is unambiguously revealed by conductive atomic force microscopy and results are attributed to the point force‐triggered Mott transition, as also confirmed by temperature‐dependent measurements. The reported features open a new avenue for developing mechano‐nociceptors, which enable a high‐level of artificial intelligence within the device to classify physical touch. Abstract : Concept of a force‐enabled nociceptive behavior is proposed and demonstrated from vanadium oxide‐based artificial receptors. Mott device can classify sharp or blunt objects and can encode harmful mechanical touch by emulating the biological counterparts of nociceptor. Point force‐triggered Mott transition is the key to realize the intent of the touch, which was supported by cAFM measurements and finite element simulations.